A Flexible Lead‐Free BaTiO3/PDMS/C Composite Nanogenerator as a Piezoelectric Energy Harvester. Issue 5 (16th April 2018) - Luo, Cuixian; Hu, Sihuan; Xia, Mengjie; Li, Pengwei; Hu, Jie; Li, Gang; Jiang, Huabei; Zhang, Wendong
Abstract: A novel approach to develop high‐performance flexible piezoelectric nanogenerators (PNGs) by using a lead‐free BaTiO3 /polydimethyl siloxane (PDMS)/C composite thin film is proposed. The lead‐free BaTiO3 nanoparticles (NPs) are successfully fabricated using a facile modified (nano‐scale precursors) solid‐phase method. The synthesized BaTiO3 /PDMS/C composite PNG exhibits an output voltage of approximately 7.43 V with periodically beating from a vibrator, which is increased by 143 % compared to the PNGs without C doping. The maximum power is shown to reach up to approximately 7.92 μW with a load resistance of 2 MΩ when the C content of PNGs is 3.2 wt %.The generated electric energy can be effectively stored by the energy storage capacitor (47 μF) and is successfully used to light a commercial red light‐emitting diode (LED). These results show that the BaTiO3 /PDMS/C composite is a promising candidate for large‐scale lead‐free piezoelectric nanogenerator applications. Abstract : Acetylene carbon black (C) is used as the conductive phase in BaTiO3 (BTO)/polydimethyl siloxane (PDMS) composite to regulate the domain structure of the sample, thereby improving the piezoelectric performance of composite. The synthesized BTO/PDMS/C composite piezoelectric nanogenerators (PNGs) exhibit a maximum output voltage of approximately 7.43 V, which is almost 2.43 times higher than that without C.